New Evidence of the Impact of Dividend Taxation and on the Identity of the Marginal Investor - Bell, Leonie; Jenkinson, Tim (Journal of Finance, 2002)
ABSTRACT This paper examines the impact of a major change in dividend taxation introduced in the United Kingdom in July 1997. The reform was structured in such a way that the immediate impact fell almost entirely on the largest investor class in the United Kingdom, namely pension funds. We find significant changes in the valuation of dividend income after the reform, in particular for high‐yielding companies. These results provide strong support for the hypothesis that taxation affects the valuation of companies, and that pension funds were the effective marginal investors for high‐yielding companies.